Occurrence of Diaretiella rapae (Mc´Intosh, 1855) (Hymenoptera: Aphidiidae) Parasitising Lipaphis erysimi (Kaltenbach, 1843) and Brevicoryne brassicae (L. 1758) (Homoptera: Aphididae) in Brassica napus in Mato Grosso do Sul - Mussury,Rosilda Mara (2002)
The occurrence of Diaretiella rapae parasitising Lipaphis erysimi and Brevicoryne brassicae in canola field (Brassica napus) was evaluated through two sample methods in Dourados-MS. The methods, used weekly, were: entomologic sweep net and plants sacking. The aphids population was observed from initial to the senescence plant development. Aphids were more abundant during the flowering phase, and they were usually located in the stems of the inflorescence and development fruits. In this phase the largest parasitism level for D. rapae (89,7%) occurred. The sample method with a sweep net captured significantly (t=4,484, P <= 0,01) more D. rapae while sacking method captured more parasitise aphids (t=2,199 with P <= 0,05) and active aphids (t=3,513, P <= 0,01).